The influence of technology transfers on the development of innovations in the process industry of Croatia (Istrian County case) - Škare, Marinko; Biberić, Sanja (Business, Management and Economics Engineering, 2015)
This paper studies the influence of technology transfers on the development of innovations in the process industry in Croatia (Istrian County case). The technological regime identifies characteristics of the learning processes, sources of knowledge and the nature of knowledge bases linked to the innovative process in the company happening as part of production activities. The research supports Schumpeter’s standpoint in his theory of creative destruction. When a new and more efficient design for the production of a commodity is created, the enterprise that first starts using the new design conquer a part of its competitors’ market. The competition reacts either by introducing the same design or one even newer or completely loses the market, as this is the case in the process industry in Croatia.